Considerations on the diffusion of Kleinian thought in Brazil - Abrão, Jorge Luis Ferreira [UNESP] (FapUNIFESP (SciELO), 2008)
This article describes the different moments that characterized the diffusion of Kleinian thought in psychoanalytic societies in Brazil. The article results from qualitative historical research based on interviews with thirteen psychoanalysts who participated in this process of diffusion. The first influences appeared in 1950, exercised by pioneers trained either in Britain or in Argentina. The areas in which the Kleinians were pioneers -psychoanalysis of children and of psychotics - were the first aspects dealt with by this group in Brazil. Between 1950 and 1970 very dogmatic approaches were taken toward Kleinian ideas. As of 1980, with the publication of new translations of Melanie Klein's work and with the introduction of contemporary Kleinian thought, a more balanced use of this theoretical-technical model could been seen.
Considerações históricas sobre a difusão do pensamento kleiniano no Brasil
Keywords: Brazil; History; Melanie Klein; Psychoanalysis